Barriers and enablers of breastfeeding in mother–newborn dyads in institutional settings during the COVID-19 pandemic: A qualitative study across seven government hospitals of Delhi, India - Maria, Arti; Mukherjee, Ritika; Upadhyay, Swati; Pratima, Kumari; Bandyopadhyay, Tapas; Gupta, Rachita; Dubey, Bhawna; Sharma, Abhinav; Mall, Pranaya Kumar; Sahoo, Manaswinee; Pathak, Keshav Kumar; Pawar, Priyanka; et al. (Frontiers in Nutrition, 2022)
Introduction: The COVID-19 pandemic disrupted newborn-care and breastfeeding practices across most healthcare facilities. We undertook this study to explore the barriers and enablers for newborn-care and breastfeeding practices in hospitals in Delhi, India for recently delivered mother (RDM)-newborn dyads during the first wave of the COVID-19 pandemic (2020) and inductively design a ‘pathway of impaction’ for informing mitigatory initiatives during the current and future pandemics, at least in the initial months. Materials and Methods: We used an exploratory-descriptive design (qualitative research method) and collected information from seven leading public health facilities of Delhi, India. We conducted separate interviews with the head and senior faculty from departments of Paediatrics/ Neonatology (n=12) and of Obstetrics (n=07), and resident doctors (n=14), nurses (labour room/ maternity ward; n=13), and RDMs (n=45) across three profiles: (a) COVID-19 negative RDM with healthy newborn (n=18), (b) COVID-19 positive RDM with healthy newborn (n=19) and (c) COVID-19 positive RDM with sick newborn needing intensive care (n=08) along with their care-giving family members (n=39). We analyzed the data using grounded-theory as the method and phenomenology as the philosophy of our research. Results: Anxiety among clients and providers, evolving evidence and advisories, separation of the COVID-positive RDM from her newborn at birth, providers’ tendency to minimise contact duration and frequency with COVID-positive mothers, compromised counselling on breastfeeding, logistic difficulties in expression and transportation of COVID positive mother’s milk to her baby in nursery, COVID-restrictions, staff shortage and unavailable family support in wards and nursery, and inadequate infrastructure were identified as major barriers. Keeping the RDM-newborn together, harmonization of standard operating procedures between professional associations and within and between departments, strategic mobilisation of resources, optimization of human resource, strengthening client-provider interaction, risk triaging, leveraging technology and leadership-in-crisis-situations were notable enablers. Conclusion: Separation of the RDM and newborn led to a cascade of disruptions to newborn-care and breastfeeding practices in the study institutions. Separating the newborn from the mother should be avoided during public health emergencies unless there is robust evidence favouring the same; routine institutional practices should be family-centred.